Lipid raft associated molecules modulate signal transduction and inflammatory mediator release in mast cells - Freitas Filho, Edismauro Garcia (2019)
Mast cells (MCs) play an essential role in innate immunity, allergy, and inflammation. The action of MCs is directly related to their release of bioactive mediators. Following activation of the high affinity IgE receptor (Fc?RI), initial signal transduction events occur in lipid rafts (LRs) in the plasma membrane. In order to better understand the important role of LR in MC function, attention was first directed towards the role of the MC specific GD1b-derived gangliosides present in LRs in modulating mediator release. Cross-linking these gangliosides with mAbAA4 activated MCs without inducing degranulation. However, ganglioside cross-linking resulted in the release of newly formed lipid mediators (prostaglandins D2 and E2) and newly synthesized mediators (interleukin-4, interleukin-6 and TNF-?). These responses were respectively due to partial activation of the arachidonate cascade and induction of MAP Kinase phosphorylation and activation of transcription factors. It then was of interest to examine the protein composition of LRs from RBL-2H3 MCs by qualitative mass spectrometry. 949 different LR proteins were identified. Functional enrichment analysis demonstrated an intimate association of these proteins with cellular membrane compartments and an involvement with MC biological processes, especially those related to regulated secretion, organization of macromolecular complexes, and signal transduction. Moreover, in this LR proteome, RACK1 was identified for the first time in MCs. RACK1 is a multifaceted scaffold protein that is a critical hub for intracellular signaling and immunoregulatory responses. Therefore, it was important to characterize the functional role of RACK1 in MCs. RACK1 knockdown in RBL-2H3 MCs affected cell morphology and resulted in a drastic rearrangement of the actin cytoskeleton with increased basal and stimulus-induced degranulation. The cortical region of the RACK1 knockdown MCs had F-actin free cortical regions, which may facilitate fusion of CD63+- secretory granules with the plasma membrane, thus explaining the increased levels of degranulation. Furthermore, RACK1 positively influences the release of newly synthesized mediators. Additionally, RACK1 depletion showed a profound impact on Ca2+-mobilization. In conclusion, this study demonstrates that the LR associated molecules, MC-specific GD1bderived gangliosides and the scaffold protein RACK1, modulate signal transduction and subsequent mediator release in MCs, providing additional information to elucidate the MC functions.